TLR9 and COVID-19: A Multidisciplinary Theory of a Multifaceted Therapeutic Target - Bezemer, Gillina F. G.; Garssen, Johan (Frontiers in Pharmacology, 2021)
By mapping the clinical pathophysiology of the novel coronavirus disease COVID-19 against insights from virology, immunology, genomics, epidemiology and pharmacology, it is here proposed that the pathogen recognition receptor called toll like receptor 9 (TLR9) might have a pivotal role in the pathogenesis of COVID-19. SARS-CoV-2, is causing the greatest global social and economic disruption since world war II. Lack of a vaccine, lack of successful treatment and limitations of the healthcare workforce and resources needed to safeguard patients with severe COVID-19 on the edge of life, demands radical preventive measures. It is urgently needed to identify drug candidates that can prevent or dampen the severe multi-organ complications in vulnerable patients with COVID-19. The TLR9 COVID-19 hypothesis describes a mechanism of action that could explain a wide spectrum of manifestations observed in COVID-19 patients. The introduced hypothesis positions TLR9 as a promising multifaceted intervention target for prevention and/or treatment of COVID-19. TLR9 agonists might have value as prophylactic vaccine adjuvants and therapeutic immune stimulators at the early onset of disease. Additionally, in this current manuscript it is proposed for the first time that TLR9 could be considered as a target of “inhibition” aimed to dampen hyperinflammation and thrombotic complications in vulnerable patients that are at risk of developing late stages of COVID-19. The readily availability of TLR9 modulating drug candidates that have reached clinical testing for other disorders could favor a fast track development scenario, an important advantage under the current high unmet medical need circumstances regarding COVID-19.